2013
DOI: 10.1002/maco.201307234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AC current on corrosion behavior of cathodically protected Q235 steel

Abstract: A self‐designed experiment circuit was adopted to investigate the effect of alternating current (AC) on corrosion rate and cathodic protection (CP) potential of cathodically protected Q235 steel in the simulated soil solution of 4 g/L sodium sulfate. It is found that the corrosion induced by AC current can be controlled by increasing CP current when AC current density is below 300 A/m2. However, in case that CP current is too large the corrosion of Q235 steel will be accelerated. Moreover, CP potential of Q235… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…It has been acknowledged [ 29 ] that DC potential is closely related to the quantity of electrons on the electrode surface. Thus, the shifting direction of the DC potential is decided by the relative magnitude of anodic and cathodic current densities of the electrode.…”
Section: Discussionmentioning
confidence: 99%
“…It has been acknowledged [ 29 ] that DC potential is closely related to the quantity of electrons on the electrode surface. Thus, the shifting direction of the DC potential is decided by the relative magnitude of anodic and cathodic current densities of the electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitation of various factors, more and more pipelines are parallel to or cross high-voltage transmission lines or electrified railways in recent years. The AC stray current caused by high-voltage transmission lines or electrified railways can induce serious corrosion in buried pipelines (Kim et al 2004;Fu and Cheng 2010;Büchler 2012;Xu et al 2012;Tang et al 2013), especially when buried pipelines are parallel to high-voltage transmission lines or electrified railways over long distances. Even with the application of cathodic protection (CP), when the pipeline coating contains microscopic defects or surface damage, corrosion of pipelines could also be very serious from the influence of AC stray current (Gummow 1999;Kajiyama and Nakamura 1999;Ibrahim et al 2007;Büchler and Schöneich 2009;Ormellese et al 2011;Fu and Cheng 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, few mechanisms have been proposed for the influence of AC on the CP potential. Du et al [ 4 , 32 ] suggested that the shifting direction of the CP potential might depend on the varying slopes of the three parts of the cathodic polarization curve, i.e., the activation control stage with low slope, the oxygen diffusion control stage with high slope, and the mixed control stage with low slope. This theory was limited to diffusion-controlled systems, and neglects the effect of anodic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, many different results have been obtained and the mechanism of AC corrosion under CP has not reached a consensus so far. Du et al [ 4 ] proved that AC corrosion can be controlled by the increase of CP current when the AC current density is below 300 A/m 2 . Similarly, Cheng et al [ 5 , 6 ] illustrated that only when the CP potential is sufficiently negative, will the steel be under a complete cathodic protection even when the AC current density is up to 400 A/m 2 .…”
Section: Introductionmentioning
confidence: 99%